2021
DOI: 10.1021/acscatal.1c02410
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective [2+2+2] Cycloaddition of Enediynes Enabled by Cobalt/Organophotoredox Cooperative Catalysis

Abstract: Herein, we report dual cobalt and photoredox catalysis enabled [2+2+2] cycloaddition of enediynes to produce tricyclic cyclohexadienes bearing a quaternary bridgehead carbon. A variety of enediynes were used, and the corresponding cyclohexadienes were obtained in good to high yields. The use of a chiral ligand, (S)-Segphos, enabled a highly enantioselective reaction allowing access to highly enantio-enriched cyclohexadienes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In general, cycloaddition of unsaturated compounds involving 1,6-diynes proceeds via a metallacyclopentadiene intermediate, followed by the insertion of a π-component and reductive elimination, to produce the cycloadduct . Recently, we have reported an asymmetric [2 + 2 + 2] cycloaddition of enediynes mediated by cobalt/photoredox dual catalysis to furnish enantioenriched tricyclic molecules (Scheme B). , During this study, we were surprised to observe that the use of an ester-tethered enediyne produced a 1-naphthol derivative selectively, albeit in low yield, while the tricyclic [2 + 2 + 2] cycloadduct was not detected. While numerous aromatic compounds have been synthesized via redox-neutral transition-metal-catalyzed cycloadditions of unsaturated acyclic compounds such as α,ω-diynes, the synthesis of 1-naphthol derivatives using this method remains rare, despite substituted 1-naphthols being an important class of structural motifs found in many bioactive natural products and pharmaceuticals .…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…In general, cycloaddition of unsaturated compounds involving 1,6-diynes proceeds via a metallacyclopentadiene intermediate, followed by the insertion of a π-component and reductive elimination, to produce the cycloadduct . Recently, we have reported an asymmetric [2 + 2 + 2] cycloaddition of enediynes mediated by cobalt/photoredox dual catalysis to furnish enantioenriched tricyclic molecules (Scheme B). , During this study, we were surprised to observe that the use of an ester-tethered enediyne produced a 1-naphthol derivative selectively, albeit in low yield, while the tricyclic [2 + 2 + 2] cycloadduct was not detected. While numerous aromatic compounds have been synthesized via redox-neutral transition-metal-catalyzed cycloadditions of unsaturated acyclic compounds such as α,ω-diynes, the synthesis of 1-naphthol derivatives using this method remains rare, despite substituted 1-naphthols being an important class of structural motifs found in many bioactive natural products and pharmaceuticals .…”
mentioning
confidence: 85%
“…On the basis of the results of the control experiments, a plausible reaction mechanism is proposed in Figure 1D. 15 23 The reductive elimination of III then proceeds to form allene 3 and regenerate the Co I catalyst, from which the Co 0 species was recovered via photocatalyst-mediated reduction. 24 Allene 3 exists in equilibrium with complex IV, which can lead to the inhibition of the reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Yamamoto and coworkers [43] reported dual photoredox and cobalt catalyst promoted [2 + 2 + 2] cycloaddition of enediynes to a tricyclic cyclohexadienes containing a quaternary bridgehead carbon. Series of enediynes were subjected to this cycloaddition reaction using catalytic amount of 4CzIPN, CoCl 2 , PPh 3 and triethylamine as base.…”
Section: Cycloadditionmentioning
confidence: 99%
“…In 2021, Yamamoto et al found an enantioselective [2+2+2] cycloaddition via dual cobalt and photoredox catalysis (187), with a chiral bisphosphine (188) as ligand. In the presence of bule light (λ = 448 nm), enediynes (189) could produce tricyclic cyclohexadienes bearing a quaternary bridgehead carbon (190) in good yields and enantioselectivity (up to 88% yield, up to >99% er) (Scheme 41) [51]. A variety of enediynes were well tolerated to obtain corresponding cyclohexadienes.…”
Section: Enantioselective Formation Of Multi-ring By Visible Light Catalysismentioning
confidence: 99%